Urgency of Executorial Beslag Institution at The Industrial Relations Court in Indonesia - Yurikosari, Andari; Amriyati, Amriyati; Pamungkas, Yogo (Green Publisher Indonesia, 2023)
The Law Number 2 of 2004 concerning Settlement of Industrial Relations Disputes regulates the settlement of disputes in the employment relationship between workers and employers, including disputes over rights, interests, termination of employment, and disputes between trade unions within one company. The Industrial Relations Court is formed to examine and decide on the industrial relations dispute, and the execution of the decision handed down will be carried out. However, the problem is how to carry out the execution in the Industrial Relations Court for decisions that have legal force, and whether it is necessary to establish a separate execution confiscation institution is regulated in the Law on the Settlement of Industrial Relations Disputes. Article 57 of the law states that the procedural law applicable to the Industrial Relations Court is the civil procedural law that applies to courts within the general court environment, unless specifically regulated in this law. The entire legal process for the settlement of industrial relations disputes uses the civil procedural legal process, including the rules regarding the execution. Several studies have highlighted the need for a separate execution confiscation institution to improve the effectiveness of the settlement of industrial relations disputes.